2015
DOI: 10.1039/c5ob00865d
|View full text |Cite
|
Sign up to set email alerts
|

Morita–Baylis–Hillman adduct derivatives (MBHADs): versatile reactivity in Lewis base-promoted annulation

Abstract: Lewis base-promoted annulation reactions with MBHADs have emerged as a key platform for the construction of functionalized carbo- and heterocycles. MBHADs, which are economical and readily available, exert diverse and amazing reactivity when reacted with a wide range of electrophiles. A variety of carbo- and heterocycles, most of which are predominant in natural products and pharmaceuticals, could be constructed with high efficiency. This tutorial review will describe these annulation reactions, with a special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(49 citation statements)
references
References 55 publications
(136 reference statements)
0
49
0
Order By: Relevance
“…Employing a nucleophilic organocatalyst [26], such as a tertiary amine or a phosphine, this simple reaction provides densely functionalized products, such as α-methylene-β-hydroxycarbonyl compounds [5056]. The aza-variant of this process consists in using an activated imine instead of an aldehyde, thus affording α-methylene-β-aminocarbonyl derivatives.…”
Section: Reviewmentioning
confidence: 99%
“…Employing a nucleophilic organocatalyst [26], such as a tertiary amine or a phosphine, this simple reaction provides densely functionalized products, such as α-methylene-β-hydroxycarbonyl compounds [5056]. The aza-variant of this process consists in using an activated imine instead of an aldehyde, thus affording α-methylene-β-aminocarbonyl derivatives.…”
Section: Reviewmentioning
confidence: 99%
“…Theu npopularity of ketimines in phosphine catalysis is likely due to their intrinsic low reactivity,s teric bulkiness,a nd the associated difficulty with stereochemical control. There are only two reports to date in which ketimines are employed for phosphine catalysis in anon-stereoselective manner, [4] and only one enantioselective example by Sasai and co-workers,which describes the use of cyclic ketimines in [4+ +2] annulation with allenoates.[5] Notably,t he cyclic ketimines utilized by Sasai et al were rather special and the reaction suffered from arelatively narrow substrate scope.As part of our continued interests in phosphine catalysis, [6] we became interested in developing an efficient strategy for the use of ketimine substrates in common phosphine-mediated annulation reactions for the construction of molecular structures of biological significance (Scheme 1).Spirooxindoles are prominent structural motifs that are often found in natural products.A mong different spirooxindole cores,t he pyrrolidinyl spirooxindole frameworks represent av ery important class owing to their excellent bioactivity profiles.Most of the current research efforts have been focused on the synthesis of 3,3'-pyrrolidinyl spirooxindoles, [7] however, 3,2'-pyrrolidinyl spirooxindoles are also undeniably important and display ab road spectrum of biological activities [8] (Scheme 2). There are only ah andful of reports describing the synthesis of 3,2'-pyrrolidinyl scaffolds, [9] and these methods either employ very specific substrates or suffer from an arrow reaction scope.Anovel approach for the efficient construction of such important structural motifs with broad substrate scope is thus highly desirable.…”
mentioning
confidence: 99%
“…There are only two reports to date in which ketimines are employed for phosphine catalysis in anon-stereoselective manner, [4] and only one enantioselective example by Sasai and co-workers,which describes the use of cyclic ketimines in [4+ +2] annulation with allenoates. [5] Notably,t he cyclic keti-mines utilized by Sasai et al were rather special and the reaction suffered from arelatively narrow substrate scope.As part of our continued interests in phosphine catalysis, [6] we became interested in developing an efficient strategy for the use of ketimine substrates in common phosphine-mediated annulation reactions for the construction of molecular structures of biological significance (Scheme 1).…”
mentioning
confidence: 99%
“…l-Threonine-derived phosphine amide catalysts (4a-4d)d isplayed remarkable catalytic activity, affording the desired spirocyclic3 -oxindolo-pyrrolines in good yields and with excellent ee values,and O-TBS-derived 4a was found to be the best catalyst (Table 1, entries 1-4). All the other amino acid based phosphines were less effective ( Table 1, entries [5][6][7][8][9]. We further tested various Nsubstituents on the ketimine scaffords and found that the N-Boc substrate 1a was the most suitable (Table 1, entries [10][11][12][13].…”
mentioning
confidence: 99%